New Zealand estuary benthic health indicators summarised nationally and by estuary type. Issue 1 (2nd January 2020) - Berthelsen, Anna; Atalah, Javier; Clark, Dana; Goodwin, Eric; Sinner, Jim; Patterson, Murray
ABSTRACT: Ecological data are often collected at small geographic scales. However, analysing data collectively over wider scales can reveal results and patterns not shown in the smaller-scale data. We summarised data for intertidal benthic ecological (physico-chemical and biological) health indicators from New Zealand estuaries and compared the results against thresholds above which ecological impacts are expected to occur. Values for the sediment physico-chemical indicators mud and nutrients (nitrogen and phosphorus collectively) were above thresholds for at least 50% and at 31% of sites measured respectively. Sediment organic content and metal concentrations were generally low, with only maximum values exceeding the thresholds. Scores for biological indicators were within (or better than) the moderate health category for either at least 50%, or at least 75%, of sites. When compared across estuary types (based on a geomorphic classification system) we found statistically significant differences for thirteen of the sixteen indicators. Differences (among mean values) for highly significant results were relatively large compared to the range of values observed nationally for those indicators. However, the differences, except those for mud, were smaller than their respective ecological health threshold values. Our summary provides a reference for future comparisons of estuary indicators nationally and across estuary types.